Assessment of Soft Skill Learning Model Instruments in Interpersonal Relations of Economic Education Students - Suratno Suratno; Zuhri Saputra Hutabarat (STAI Hubbulwathan Duri, 2023)
The purpose of this research and development was to produce a product of Soft Skills Model Assessment Instruments regarding interpersonal relationships of economic education students and to know the characteristics of the soft skills learning model assessment instruments related to interpersonal relationships. The feasibility of the Soft Skills Model assessment instrument is assessed based on the level of validity of the experts regarding the draft soft skills instrument of economics students. The data collection instruments used included expert validation sheets, student response questionnaires, assessment sheets and observation sheets. The research method used in the development of the Soft Skills Model Assessment Instrument regarding the interpersonal relationships of economic education students was research and development referring to the ADDIE model developed by Lee and Owen. Several stages that will be carried out in this research and development are (1) Needs Analysis, (2) Soft skill instrument development design, (3) Soft Skill instrument development, (4) Soft skill instrument evaluation model implementation, (5) and Model Evaluation Soft skill assessment instrument for economic education students. The findings of this research and development from instrument experts on the assessment instrument for the soft skills learning model of economic education students concluded the validation of the experts who stated that it was very valid with an average percentage score of 86.36%. Then it is also shown that the results of small groups and student responses of 86.52% are included in the very good category.